2015
DOI: 10.1016/j.vph.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-lipoic acid activates eNOS through activation of PI3-kinase/Akt signaling pathway

Abstract: Background Lipoic acid (LA) exerts therapeutic effects on cardiovascular diseases. However, the mechanisms underlying these therapeutic effects remain elusive. Endothelial nitric oxide synthase (eNOS) plays a critical role in cardiovascular homeostasis. LA was shown to potently activate PI3-kinase/Akt pathway, and the latter is critical in the regulation of eNOS activity. In the present study, we test the hypothesis that LA improves endothelial function through PI3-kinase/Akt-mediated eNOS activation. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 29 publications
(57 reference statements)
1
14
0
Order By: Relevance
“…As shown in Figure 5, eight target genes of 16 miRNAs are involved in the PI3K pathway across seven cancer types, based on KEGG (Release 79.1, http://www.genome.jp/kegg/) and studies from Waugh MG [58], Ying Z et al . [59], and Yun YR et al . [60].…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 5, eight target genes of 16 miRNAs are involved in the PI3K pathway across seven cancer types, based on KEGG (Release 79.1, http://www.genome.jp/kegg/) and studies from Waugh MG [58], Ying Z et al . [59], and Yun YR et al . [60].…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been observed that LA activates eNOS by activating Akt signaling (34). By contrast, inhibition of Akt signaling by high levels of UA may be associated with UA-induced insulin resistance, indicating that Akt signaling serves an essential role in endothelial cell function (35).…”
Section: Discussionmentioning
confidence: 99%
“…PTEN, an important tumor suppressor, is a negative regulator of the PI3K pathway [50]. As shown in Figure 5 [52], and Yun YR et al [53]. miRNAs involved in regulating FGFR family members were also shown in Figure 5, adding another potentially important miRNA, hsa-mir-381, to the pathway.…”
Section: Construction Of Regulatory Network Of Sdemirnas and Their Tmentioning
confidence: 93%